2021
DOI: 10.15406/jlprr.2021.08.00250
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ACE-2 enzyme by hyperoxia in lung epithelial cells by post-translational modification

Abstract: Background: Bronchopulmonary Dysplasia (BPD) occurs in premature neonates with respiratory distress who require supplemental oxygen in the first days after birth. BPD involves uniform arrest of alveolar development and variable interstitial cellularity and/or fibroproliferation. Previous studies by our lab showed that the enzyme, angiotensin converting enzyme-2 (ACE-2) and its product Ang1-7 exerting action on the receptor Mas oncogene in what is known as ACE-2/Mas axis is protective to lung cells. We also sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Here we investigated ACE2 ubiquitination as a strategy to identify potential upstream regulators of ACE2 protein abundance. Most cellular proteins undergo posttranslational modification with ubiquitin; ACE2 is no exception ( 7 , 15 ). More recently, studies have demonstrated ACE2 ubiquitination in SARS-CoV-2 infection and identified E3 ligases Skp2 ( 16 ) and UBR4 ( 17 ) as putative regulators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we investigated ACE2 ubiquitination as a strategy to identify potential upstream regulators of ACE2 protein abundance. Most cellular proteins undergo posttranslational modification with ubiquitin; ACE2 is no exception ( 7 , 15 ). More recently, studies have demonstrated ACE2 ubiquitination in SARS-CoV-2 infection and identified E3 ligases Skp2 ( 16 ) and UBR4 ( 17 ) as putative regulators.…”
Section: Discussionmentioning
confidence: 99%
“…In pulmonary hypertension, ACE2 is ubiquitinated by MDM2 to regulate its abundance, which may impact pulmonary hypertension pathogenesis ( 7 ). ACE2 ubiquitination is also modified by hyperoxia in the lung ( 15 ). The E3 ligase Skp2 has also been proposed to degrade ACE2 in the setting of cigarette smoke extract ( 16 ).…”
mentioning
confidence: 99%
“…For example, ACE2 shows the highest levels in the kidney, small intestine and adipose tissues, the medium levels in the lung, colon and liver tissues, and the lowest levels in the brain, bone marrow and blood (Li et al, 2020). Thus, we observed ACE2 protein levels in several cell lines from different tissues, including HEK293T (kidney), A549 (lung) and Caco-2 (colon), as well as a human fibroblast cell line (2fTGH) due to the reported expression of ACE2 in lung fibroblasts (Mohamed et al, 2021), since these cell lines have been reported to be functional for SARS-CoV-2 infection. We noticed that all these cell lines can more or less express ACE2 proteins (Figure 1A).…”
Section: Resultsmentioning
confidence: 90%
“…For example, ACE2 shows the highest levels in the kidney, small intestine, and adipose tissues; medium levels in the lung, colon, and liver; and the lowest levels in the brain, bone marrow, and blood (Li et al , 2020b). Thus, we measured ACE2 protein levels in several cell lines derived from different tissues, including HEK293T (kidney), A549 (lung), and Caco‐2 (colon) cells, as well as a human fibroblast cell line (2fTGH) due to the reported expression of ACE2 in lung fibroblasts (Mohamed et al , 2021), since these cell lines have been reported to be functional for SARS‐CoV‐2 infection. We found that all these cell lines expressed the ACE2 protein to varying degrees (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%